The Role of Mobile Library Program and Learning Assistance in Increasing Literacy Interest of Elementary Student at Cimaja Village - Futri, Dila Aura; Insany, Gina Purnama; Medal Wangi, Shanika Layung; Munggaran, Dava Febrian; Bunga, Siti; Naufal, Ripki Tri (Edumedia Solution, 2024)
Cimaja Village has a low literacy rate of only 53%, which is concerning because it shows a gap in the community's access to education and comprehension of information. Early literacy program implementation for primary school students can benefit the village's development and provide a solid basis for later, more complex learning. The KKN Cimaja Village group organizes mentoring and mobile library programs at Cimaja Village, Sukabumi Regency, with the goal of enhancing literacy among elementary school students. Learning about reading, writing, and numeracy is integrated through the use of the Balanced Literacy approach. The primary school pupils at Cimaja Village have embraced this program wholeheartedly. Students' reading skills have significantly improved, according to observations.